Collision Avoidance in Swarm of UAVs - Karki, Apil (fi=Turun yliopisto|en=University of Turku|, 2017)
The objective of this thesis was to develop a prototype which avoids the collision in an indoor and outdoor environment and establish communication between the swarm of unmanned aerial vehicles(UAVs). This thesis introduces the collision sensing, detection, and avoidance system using an ultrasonic sensor, communication between the swarm of UAVs was established using APC220 telemeters and network sockets embedded in Raspberry Pi3. Several basic theories of the swarm of UAVs, collision avoidance methods and its effects have been studied and explained. We have used carrier sense multiple access to avoid the interference between the sensors and used different measurement cycles. We have also presented relation between a number of collisions avoided and energy consumption of the drone. Unique ID for drones has been created using network sockets to distribute the task, notify the addition of drones from same or different networks. All the experiments were carried out in an indoor environment.
Department of Future Technologies